Interpreters with Lewis and Clark : the story of Sacagawea and Toussaint Charbonneau - Nelson, W. Dale. (Denton, Tex. : University of North Texas Press, 2003)
A frank portrayal of Toussaint Charbonneau, a French-Canadian fur trader, who, with his Shoshone Indian wife Sacagawea, joined the Lewis and Clark expedition in 1803. While Sacagawea assumed legendary status as a "token of peace", Toussaint has been maligned in fiction and nonfiction alike
Interpreters with Lewis and Clark; Contents; List of Illustrations; Acknowledgments; Introduction; CHAPTER ONE The Meeting; CHAPTER TWO Winter; CHAPTER THREE Against the Current; CHAPTER FOUR Over the Top; CHAPTER FIVE Fort Clatsop; CHAPTER SIX Homeward Bound; CHAPTER SEVEN Afterward; CHAPTER EIGHT Father and Son; CHAPTER NINE At Home and Abroad; CHAPTER TEN The Prince and the Frontiersman; CHAPTER ELEVEN Glimpses of Baptiste; CHAPTER TWELVE Desolation on the Missouri; CHAPTER THIRTEEN Westward Once More; CHAPTER FOURTEEN John B. Charbonneau; Epilogue; Notes; Bibliography; Index.
Includes bibliographical references (pages 157-168) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Sacagawea; Sacagawea -- Family; Charbonneau, Toussaint, -- approximately 1758-approximately 1839.; Charbonneau, Jean-Baptiste, -- 1805-1866.; Charbonneau, Jean-Baptiste, -- 1805-1866; Charbonneau, Toussaint, -- approximately 1758-approximately 1839; Sacagawea; Sacagawea; Sacagawea; Charbonneau, Toussaint, -- ca. 1758-ca. 1839.; Shoshoni women -- West (U.S.) -- Biography; Pioneers -- West (U.S.) -- Biography; Indian interpreters -- West (U.S.) -- Biography; West (U.S.) -- Discovery and exploration; Frontier and pioneer life -- West (U.S.); TRAVEL -- General; TRAVEL; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; Discoveries in geography; Families; Frontier and pioneer life; Indian interpreters; Pioneers; Shoshoni women; West United States; Lewis-and-Clark-Expedition; Ontdekkingsreizigers; Indianen; Ontdekkingsreizen; États-Unis (Ouest) -- Découverte et exploration; Shoshoni women -- West (U.S.) -- Biography; Translating and interpreting -- Biography; Biographies; Biographies; Biographies